Using semantic mapping to teach ESP vocabulary to final-year students of finance and accounting at Hanoi tourism college = Sử dụng sơ đồ ngữ nghĩa để dạy từ vựng tiếng Anh chuyên ngành cho sinh viên năm cuối, chuyên ngành tài chính và kế toán, trường Cao - Phạm, Thị Hạnh (University of Languages and International Studies, 2017)
45 p. + CD-ROM